Classification of Rectus Diastasis—A Proposal by the German Hernia Society (DHG) and the International Endohernia Society (IEHS) - Reinpold, Wolfgang; Köckerling, Ferdinand; Bittner, Reinhard; Conze, Joachim; Fortelny, René; Koch, Andreas; Kukleta, Jan; Kuthe, Andreas; Lorenz, Ralph; Stechemesser, Bernd (Frontiers in Surgery, 2019)
Introduction Recently, the promising results of new procedures for the treatment of rectus diastasis with concomitant hernias using extraperitoneal mesh placement and anatomical restoration of the linea alba were published. To date, there is no recognized classification of RD with concomitant hernias. This is urgently needed for comparative assessment of new surgical techniques. A working group of the German Hernia Society (DHG) and the International Endohernia Society (IEHS) set itself the task of devising such a classification. Methods A systematic search of the available literature was performed up to October 2018 using Medline, PubMed, Scopus, Embase, Springer Link, and the Cochrane Library. A meeting of the working group was held in May 2018 in Hamburg. For the present analysis 30 publications were identified as relevant. Results In addition to the usual patient- and technique-related influencing factors on the outcome of hernia surgery, a typical means of rectus diastasis classification and diagnosis should be devised. Here the length of the rectus diastasis should be classified in terms of the respective subxiphoidal, epigastric, umbilical, infraumbilical and suprapubic sectors affected as well as by the width in centimeters, whereby W1 = < 3 cm, W2 = 3 ≤ 5 cm and W3 = > 5 cm. Furthermore, gender, the concomitant hernias, previous abdominal surgery, number of pregnancies and multiple births, spontaneous birth or caesarian section, skin condition, diagnostic procedures and preoperative pain rate and localization of pain should be recorded. Conclusion Such a unique classification is needed for assessment of the treatment results in patients with RD.